Assessing routine healthcare pattern for type 2 diabetes mellitus in Russia: the results of рharmacoepidemiological study (FORSIGHT-DM2) - Ivan I. Dedov; Marina F. Kalashnikova; Dmitriy Y. Belousov; Vladimir V. Rafalskiy; Victor Y. Kalashnikov; Aleksey S. Kolbin; Diana R. Yazykova; Leonid R. Ivanenko (Сахарный диабет)
Rationale. The rising incidence of type 2 diabetes mellitus (T2DM) allows researchers to conduct observational multicentre studies and obtain objective information about the epidemiology of diabetes and its complications and evaluate the efficacy of different therapies and diagnostic strategies designed to identify systemic vascular complications.Aims. To analyse epidemiological and socio-demographic parameters, the quality of glycaemic control, diagnostic monitoring and therapeutic measures typical among patients with T2DM living in Russian towns of different populations.Materials and methods. FORSIGHT-DM2 is an all-Russian multicentre observational epidemiological study that involves 2014 patients with T2DM from 45 different towns in the Russian Federation (RF). All patients have had T2DM for at least 1 year. They received glucose-lowering therapy and primary medical care from RF public outpatient health institutions between 01.01.2014 and 31.12.2014. For comparative analysis of the typical treatment for patients with T2DM, we stratified patients into groups based on the number of residents.Results. The data reveal a lack of glycaemic control (average НbА1с 7.9% ± 1.9%), with НbА1с > 8% in 36% of patients. The frequency of T2DM complications was high and the prevalence of retinopathy was 63.2%, nephropathy was 34.4% (7.8% had chronic kidney disease G3a-G5), peripheral polyneuropathy was 63.3%, ‘diabetic foot’ syndrome was 13.7% and osteoarthropathy was 5%. The number of T2DM-related complications is correlated with the HbA1c level and disease duration. Moreover, simultaneous influence of these factors led to a significant increase in the number of chronic complications associated with T2DM (r = 0.338 for T2DM duration, r = 0.262 for HbA1c; р < 0.001). Despite the high frequency of patient consultations with endocrinologists (83%) and a large percentage of hospitalisations in the current year (46%), the screening of chronic complications of T2DM in 2014 is insufficient.Conclusion. The results indicate insufficient glycaemic control among patients with T2DM and a higher prevalence of chronic complications compared with the national register of diabetic patients.